Cardiopulmonary exercise testing in patients with pulmonary hypertension: clinical recommendations based on a review of the evidence. (3rd March 2016) - Pinkstaff, Sherry O; Burger, Charles D; Daugherty, John; Bond, Samantha; Arena, Ross
ABSTRACT: Pulmonary hypertension (PH) remains an ominous diagnosis despite advances in pharmacological and surgical therapy. Early and effective diagnosis is important for clinicians making treatment determinations and patients wishing to understand the prognostic implications of their illness. Cardiopulmonary exercise testing (CPX) has the power to reveal the underlying pathophysiological consequences of the disease process. Research, especially over the last 10-15 years, has demonstrated the utility of this tool. Several CPX variables have been shown to be consistently altered in patients with PH and more so as severity of disease increases. However, to further enhance clinical application, additional research is needed to better define optimal CPX measures and associated cutoff values. This paper gives class-based recommendations with associated levels of evidence for the use of CPX in the PH patient population.